Development of Physics Module Based on The Batak Toba Culture on Momentum and Impulse Materials - Novia Sinaga; Rahmatsyah Rahmatsyah (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2022)
This development research focuses on making physics modules on momentum and impulse materials based on the Toba Batak culture that meets usage standards and obtains user responses to the developed modules. The type of research is research and development (R&D) according to the ADDIE model. The collection of validation data includes aspects of material content and aspects of module design. User response data includes aspects of convenience, attractiveness, and benefits. Validation data analysis uses the percentage technique while the user response is based on the average score of the research aspect. The results of the module validation based on the assessment of the material experts obtained very feasible criteria with an overall ratio of 85.8% and the results of the design expert's review obtained very feasible criteria with an overall percentage of 96.5%. The teacher's response to the use of the module was found to be very easy, very interesting, and very useful. Meanwhile, user responses from class XI MIA 1 students are included in the criteria of being easy, interesting, and very useful. For Class XI students, MIA 2 is included in the criteria of very easy, very interesting, and very useful. The physics module based on the Toba Batak culture that was developed was stated to be very feasible, easy for users, interesting, and very useful for use in momentum and impulse learning in Class XI MIA senior high school.